1998
DOI: 10.1148/radiology.206.3.9494491
|View full text |Cite
|
Sign up to set email alerts
|

Intussusception in children: reduction with repeated, delayed air enema.

Abstract: Repeated, delayed pneumatic reduction of intussusception improves the outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
31
0
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(38 citation statements)
references
References 0 publications
4
31
0
3
Order By: Relevance
“…We consider this appropriate because studies have shown that although the probability of reduction falls with longstanding intussusception, a successful reduction is still possible [23][24][25][26][27]. Research has also shown that although likelihood of success with free or trapped fluid is relatively low, success is still possible [28,29], and the vast majority (86%) of our respondents said they attempt reduction despite the presence of free fluid.…”
Section: Discussionmentioning
confidence: 94%
“…We consider this appropriate because studies have shown that although the probability of reduction falls with longstanding intussusception, a successful reduction is still possible [23][24][25][26][27]. Research has also shown that although likelihood of success with free or trapped fluid is relatively low, success is still possible [28,29], and the vast majority (86%) of our respondents said they attempt reduction despite the presence of free fluid.…”
Section: Discussionmentioning
confidence: 94%
“…Although it might also produce perforation, the negative effect would have been milder. 7,8 The second patient was discharged on the 6 th day of hospitalization after surgical reposition was performed.…”
Section: Discussionmentioning
confidence: 99%
“…Non-surgical reduction of intussusception is generally made under fluoroscopic guidance [27][28][29][30], even if USguided reduction may represent in the future a valid alternative to fluoroscopy as a less invasive guide in nonsurgical reduction of intussusception, avoiding exposition to ionizing radiations of little patients. The best studies about the use of US guide in intussusception reduction come from Asia, but nowadays also Europe is considering this technique.…”
Section: Discussionmentioning
confidence: 99%